Payback on Poplar Lane - Mincks, Margaret (Poplar kids, 2018)
A friendly neighborhood business competition between sixth-graders Rachel Chambers, so quiet she is practically invisible, and Peter S. Gronkowski, future mogul, turns into a ruthless rivalry.